Performa Reproduksi Sapi Persilangan Berdasarkan Ketepatan Waktu IB Di Desa Angsanah Kecamatan Palengaan Kabupaten Pamekasan - Bambang Kurnadi; Malikah Umar (Maduranch : Jurnal Ilmu Peternakan, 2023)
Cattle are one of the primary needs in order to meet the needs of meat. To meet the needs of beef, it is necessary to increase the cattle population as an effort to meet the needs, so the government launched a program, namely Artificial Insemination. Artificial Insemination (AI) is the process of inserting sperm into the female reproductive tract with the aim of making the female pregnant without the need for natural mating to occur. This study aims to determine the reproductive performance of crossbreed cattle based on timeliness of AI. This research was conducted in Angsanah Village, Palengaan District, Pamekasan Regency. This research is a quantitative descriptive study with a total sample of 87 acceptors. Reproduction performance based on service per conception (S/C) and conception rate (CR). The results showed that the S/C and CR numbers at IB 1-8 hours, 9-16 hours and 19-24 hours respectively were S/C 1.1; 1.06; and 1.2 while CR 86%; 93% and 78%. From the results of research data that the best implementation of AI time is 9 -16 hours after the cattle lust.